Logistics Service Mix In Improving Business: Case Study on CV. 555 EXPRESS - Muflikhah, Muflikhah (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to determine the competitiveness of businesses in increasing the mix in t rovision of services and the development of global logistics businesses in the field of service provian and logistics services.This research is a qualitative descriptive study of the importance of the role of the Logistics Service M in increasing business competitiveness in the CV. 555 EXPRESS company affiliated with the theory op increasing business competitiveness in Indonesia is currently experiencing significant good changes, rapid growth of ecommerce can open up opportunities for companies engaged in the electronic comma business in the logistics sector. Because at this time there are poly companies providing goods delivery services that can be accessed easily from the wider community. The level of service that is not ynchronized will of course be a consideration for users of delivery services, where every costume definitely expects the best service